CORRELATION BETWEEN SELF-REGULATED LEARNING AND ACADEMIC ACHIEVEMENT OF CHEMISTRY EDUCATION STUDENTS OF FKIP SRIWIJAYA UNIVERSITY - EDI, RODI (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this research are to identify the self-regulated learning, academicachivement, the mostly used aspects of self-regulated learning, and the correlactionbetween the self-regulated learning and academic achievement of chemistry educationstudents of FKIP Unsri. This research is acorrelational study. The sample of thisresearch is the 72 students of chemistry education chosen randomly. The data weregathered by using questionnaire and documentation. The results of this research showedthat the chemistry education students had high self-regulated learning, highly satisfiedGPA and mostly used 5 out of 7 aspects of self-regulated learning. The statisticalanalysis showed that there was no significant correlation between self-regulatedlearning and academic achievement of chemistry education students. However, one outof the 7 aspects of self-regulated learningâevaluting the effectiveness--correlatedsignificantly to the studentsâ academic achievement.